2017
DOI: 10.2147/dmso.s122110
|View full text |Cite
|
Sign up to set email alerts
|

Different consecutive training protocols to design an intervention program for overweight youth: a controlled study

Abstract: ObjectiveTo find the optimal exercise program to be recommended in reducing adiposity and promoting long-term physical activity adherence in a sample of overweight adolescents.MethodsForty-five overweight adolescents were randomly divided into three exercise groups, to perform two phases of physical activity as follows: in the first phase, the first group performed a 16-week moderate-intensity resistance training (RT), the second group performed a 16-week high-intensity RT, and the third group performed a 16-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 35 publications
(40 reference statements)
1
26
0
1
Order By: Relevance
“…Of the 6478 citations screened after removing duplicates both electronically and manually, 57 studies representing 127 groups (73 exercise, 54 control) and 2792 participants (1667 exercise, 1125 control) met the criteria for inclusion 13–40 42–69 98. The number needed to screen was 0.88% while the NNR was 114.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 6478 citations screened after removing duplicates both electronically and manually, 57 studies representing 127 groups (73 exercise, 54 control) and 2792 participants (1667 exercise, 1125 control) met the criteria for inclusion 13–40 42–69 98. The number needed to screen was 0.88% while the NNR was 114.…”
Section: Resultsmentioning
confidence: 99%
“…The included studies were published in 45 different journals since 1997 ( trueX- ± SD = 2011±4, median=2012). Fifty-two studies (91.2%) were published in the English language,13 14 16–18 20 22 24–40 42–69 while the remaining five (8.8%) were published in either Chinese19 21 23 98 or Spanish 15. The location in which studies were conducted included 20 different countries, 12 in the USA,24 30 34 35 39 40 46 48 52 56 60 66 8 in China,19–23 38 61 62 98 6 in Brazil,13 15 45 47 58 63 5 in South Korea,36 37 49 55 59 4 in Tunisia,17 25 50 51 3 each in Australia,54 64 65 Canada14 32 57 and Iran,27 29 69 2 in Turkey,33 53 and 1 each in either France,16 Germany,44 Italy,28 Lebanon,68 New Zealand,42 Norway,18 Singapore,67 Sweden,31 Switzerland,26 Taiwan22 or the UK 43.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Los efectos positivos se mantuvieron, incluso, después de 12 semanas de seguimiento con mayor adherencia a la actividad física en comparación con los que participaron en el entrenamiento aeróbico exclusivo. 46…”
Section: Beneficios Del Entrenamiento De La Fuerza En Pacientes Con Sunclassified
“…Clinical eating disorders might have revealed in precursor symptoms as bradycardia and evident dehydration (Joy, Kussman, & Nattiv, 2016), and an early identification and early appropriate treatment may prevent the development of more serious problems (de Oliveira, 2017). Some authors reported that disordered eating behaviors, and also dieting, can predict not only eating disorders but also a number of problematic outcomes, including increased risk for weight gain and obesity both in adolescents and young adults (Fiorilli et al, 2017;Neumark-Sztainer, Wall, Larson, Eisenberg, & Loth, 2011). Eating disorders are more prevalent among athletes than non-athletes (Joy et al, 2016).…”
Section: Introductionmentioning
confidence: 99%